ANALISIS PENGARUH KETERSEDIAAN UANG DAN WAKTU, LINGKUNGAN TOKO, NILAI BELANJA HEDONIS, DAN EMOSI POSITIF TERHADAP PEMBELIAN TAK TERENCANA (Studi Kasus pada Pelanggan Lottemart di Kota Jakarta) - Prasetya, Aries; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2016)
This research is motivated by intense competition in the modern retail industry in Indonesia. That is because a lot of new faces emerging modern retail players. However, there is one thing on consumer purchasing behavior in modern retailing that steal the show. Most consumers in major cities in Indonesia experiencing unplanned purchase ehrn shopping.The purpose of this study is to determine the influence of variables Availability of Money and Time, Store Environment, Hedonic Shopping Value, and Positive Emotions. Variable Availability of Money and Time, Store Environment, Hedonic Shopping Value, and Positive Emotions as an independent variable; and Impulse Buying as the dependent variable.The population used in this research is the consumer of Lottemart Jakarta. This research method using a non-probability sampling technique by purposive sampling method. Used as a sample 100 respondents. Data obtained from the questionnaire which is then processed and analyzed using multiple linear regression analysis through SPSS program.The results showed that all four of independently variable has a positive influence on impulse buying. Of the four independent variables influence the Positive Emotions has the greatest impact on Impulse Buying.